Pengaruh Penggunaan Smartphone Terhadap Perubahan Postur Tubuh pada Gen Z - Aulia Deswita; David Arifin; Hilmi Rabbani Ferdi; Daffa Satrio Utomo (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Technological advancements, particularly smartphones, have brought significant changes to modern society. Smartphones serve as multifunctional tools that facilitate various daily activities, such as communication, internet access, and gaming. However, despite their many benefits, excessive smartphone use can lead to negative effects, including addiction and health issues. Data shows that 90% of individuals aged 15-24 own smartphones, with an average internet usage time of 7 hours and 38 minutes per day. Prolonged use of smartphones has the potential to affect posture, causing neck pain, shoulder pain, back pain, and headaches. Improper posture while using smartphones often results in muscle tension in the neck and upper back areas. This abstract aims to highlight the relationship between intensive smartphone use and its impact on the physical health of Generation Z, as well as the importance of maintaining proper posture when using these devices